Oxidative functionalization of a halimane diterpenoid achieved by fungal transformation - Monteiro, Afif Felix [UNESP]; Righetto, Gabriela Marinho; Simões, Laura Vilar [UNESP]; Almeida, Larissa Costa de; Costa-Lotufo, Letícia Veras; Camargo, Ilana Lopes Baratella da Cunha; Castro-Gamboa, Ian [UNESP] (Elsevier, 2019)
Regio and stereoselective activation of sp 3 C–H bonds remain one of the major advantages of biocatalysis over traditional chemocatalytic methods. Herein, we describe the oxy-functionalization of halimane diterpenoid 1 by whole cells of three filamentous fungi, aiming to obtain derivatives with desirable biological properties. After incubating 1 with Fusarium oxysporum, Myrothecium verrucaria, and Rhinocladiella similis at different concentrations and incubation times, four known (3, 5, 6, and 7) and three new (2, 4, and 8) halimane derivatives were obtained and characterized. F. oxysporum catalyzed the hydroxylation of positions C-2 (2) and C-7 (4), while R. similis simultaneously mediated the 2-oxo-functionalization and the hydration of 13,14-(C–C)double bond belonging to an α,β-unsaturated carbonyl system (8). Compounds 1–7 were non-cytotoxic against HCT-116 and MCF-7 cancer cell lines at tested concentrations. However, substrate 1 displayed moderate reduction ability against biofilm produced by Staphylococcus epidermidis ATCC35984 (84% at 1.6 mM), and this effect was retained to some extent by derivatives 4 and 7. These results emphasize the prominent potential of filamentous fungi associated with the microbiota of medicinal plants as versatile catalysts for singularly useful reactions through their complex enzymatic machinery, as well as the high susceptibility of halimane-diterpenoid substrates.
Keywords: Biofilm reduction; C–H oxidation; Double-bond hydration; Halimane diterpenoid; Microbial transformation